PEMBENTUKAN SIFAT OPTIS AKTIF MENGGUNAKAN MEDAN RADIO FREQUENCY (RF) PADA LARUTAN GARAM - Kamil, Ahmad; Azam, M.; Firdausi, K. Sofjan (BERKALA FISIKA, 2007)
The non-linear optical property of rotary power of light polarization in water and salt solution has been developed using the Radio-Frequency field (RF-Field). The RF-Field used in the experiment is produced by RF generator, and it supplies the frequency in the range between 6.04 to 14.56 MHz, which then applies to the samples. The source of light with 632.8 nm-wavelength and 532 nm-wave length are used to observe the change of angle polarization of the light, after it passes through the samples. Three modes of the direction of the electric field of light are chosen 0o (E//) (E of light is parallel to E of RF-Field, and 90o (E^) (E of light is perpendicular to E of the RF-Field) in order to determinate the optimal change of the angle of the polarization. The values of is measured as a function of RF-Field, , where is the angular frequency of RF-Field and BRF is the magnitude of magnetic field measured in the center of the coil which is assumed to be homogeny in the circumstances of the samples. The results of the experiment show that the degrees of change of the polarization direction, is largest at the mode. It shows also that at small wavelength of light we obtain the larger, which is indicated the higher frequency of light will more induce the dipoles of molecules of the samples. Keywords: non-linear optics, polarization angle, rotary power